A comparison of immunoglobulin IGHV, IGHD and IGHJ genes in wild‐derived and classical inbred mouse strains. Issue 10 (6th October 2019) - Watson, Corey T; Kos, Justin T; Gibson, William S; Newman, Leah; Deikus, Gintaras; Busse, Christian E; Smith, Melissa L; Jackson, Katherine JL; Collins, Andrew M
Abstract: The genomes of classical inbred mouse strains include genes derived from all three major subspecies of the house mouse, Mus musculus . We recently posited that genetic diversity in the immunoglobulin heavy chain (IGH) gene loci of C57BL/6 and BALB/c mice reflects differences in subspecies origin. To investigate this hypothesis, we conducted high‐throughput sequencing of IGH gene rearrangements to document IGH variable (IGHV), joining (IGHJ) and diversity (IGHD) genes in four inbred wild‐derived mouse strains (CAST/EiJ, LEWES/EiJ, MSM/MsJ and PWD/PhJ) and a single disease model strain (NOD/ShiLtJ), collectively representing genetic backgrounds of several major mouse subspecies. A total of 341 germline IGHV sequences were inferred in the wild‐derived strains, including 247 not curated in the international ImMunoGeneTics information system. By contrast, 83/84 inferred NOD IGHV genes had previously been observed in C57BL/6 mice. Variability among the strains examined was observed for only a single IGHJ gene, involving a description of a novel allele. By contrast, unexpected variation was found in the IGHD gene loci, with four previously unreported IGHD gene sequences being documented. Very few IGHV sequences of C57BL/6 and BALB/c mice were shared with strains representing major subspecies, suggesting that their IGH loci may be complex mosaics of genes of disparate origins. This suggests a similar level of diversity is likely present in the IGH loci of other classical inbred strains. This must now be documented if we are to properly understand interstrain variation in models of antibody‐mediated disease. Abstract : To better understand the subspecies origin of antibody genes in classical inbred mouse strains, the IGH gene loci of four wild‐derived mouse strains and a single disease model strain were explored by analysis of VDJ gene rearrangements. A total of 425 IGHV gene sequences were inferred in these strains, including 248 sequences that have not previously been reported. Additional diversity was identified within the IGHD and IGHJ loci. These data highlight our lack of understanding of the IGH loci of the laboratory mouse, with implications for the interpretation of strain‐specific differences in models of antibody‐mediated diseases, and of adaptive immune receptor repertoire sequencing data.